Gold Nanoparticles Disrupt Zebrafish Eye Development and Pigmentation - Kim, Ki-Tae (Oxford University Press, 2013)
Systematic toxicological study is still required to fully understand the hazard potentials of gold nanoparticles (AuNPs). Because their biomedical applications are rapidly evolving, we investigated developmental toxicity of AuNPs in an in vivo embryonic zebrafish model at exposure concentration ranges from 0.08 to 50mg/l. Exposure of zebrafish embryos to 1.3nm AuNPs functionalized with a cationic ligand, N,N,N-trimethylammoniumethanethiol (TMAT-AuNPs), resulted in smaller malpigmented eyes. We determined that TMAT-AuNPs caused a significant increase of cell death in the eye, which was correlated with an increase in gene expression of p53 and bax. Expression patterns of key transcription factors regulating eye development (pax6a, pax6b, otx2, and rx1) and pigmentation (sox10) were both repressed in a concentration-dependent manner in embryos exposed to TMAT-AuNPs. Reduced spatial localization of pax6a, rx1, sox10, and mitfa was observed in embryos by whole-mount in situ hybridization. The swimming behavior of embryos exposed to sublethal concentrations of TMAT-AuNPs showed hypoactivity, and embryos exhibited axonal growth inhibition. Overall, these results demonstrated that TMAT-AuNPs disrupt the progression of eye development and pigmentation that continues to behavioral and neuronal damage in the developing zebrafish.